Effect of High Pressure Processing on Physical Properties of Brined Chicken Breasts - Chotyakul, Nattaporn; Tanakamolpradit, Tanita (Journal of Food Technology, Siam University, 2023)
High Pressure Processing (HPP) is a promising way to tenderize meat. HPP treatment at 100, 200 and 300 MPa for 10 min was employed to study 10% and 20% brined chicken breasts (RTC meats), thereafter HPP pasteurization treatment at 90±2 °C for 20 min (RTE meats). The results showed that pressure treatment above 200 MPa induced significantly (p≤0.05) the RTC meat texture for 10% brine with harder but higher springiness than 20% brine. The chewiness showed higher in 10% brine than 20% brine at 300 MPa. Meat color was significantly effected (p≤0.05) by HPP at 300 MPa with increasing L* value for both 10% and 20% RTC meats. The redness (a*) value only affected RTE meats for 10% and 20% RTE when the pressure increased to 200 and 300 MPa. A significant (p≤0.05) increase was found in 10% and 20% RTC meats when treated with 300 MPa.